Possibilities to derive empirical dough characteristics from fundamental rheology. (November 2016) - Tietze, Stefan; Jekle, Mario; Becker, Thomas
Abstract: Background: The determination of dough properties is essential for the estimation of dough processing, dough handling behavior and future bread properties. Several methods are available for the analysis of these values. These include empirical rheological methods like torque recording during mixing, extensibility measurement or fundamental rheological methods. All have in common that the dough specimen needs to be transferred from one device to another. This leads to an additional incorporation of mechanical energy and by that to an alteration of the dough structure. As a result, the measurement data can be defective. Scope and approach: This review describes the working principles of the traditional empirical methods and shows how the additional energy input can be avoided. In order to avoid alteration of data different measurement techniques are discussed that can be performed in one device and that deliver correct information about the dough properties. Key findings and conclusions: Instead of common correlations, real physical and mathematical connections and links are shown in order to derive the values of the classical dough testing methods by fundamental rheological measuring techniques. These equations are the base for a successful data conversion between empirical and fundamental rheological methods. The reliable data conversion is crucial for a successfully working measurement technique that can be performed in a single conventional rheometer. This eliminates unwanted data alteration and assures proper machine settings for dough handling. Highlights: Dough production, processing and examination can be combined in one device. The processing steps can be carried out in a conventional rheometer. Links between empirical and fundamental dough rheology are worked out. Processing and examination will be free from alteration of data. An all-in-one method for dough characterization is proposed.